A Survey Of Post Immunization Affairs (AEFI) Of Astrazeneca Vaccine In The Community In The Work Area of Sedayu II Puskesmas, Bantul, Yogyakarta - Nessy Anggun Primasari (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2024)
Introduction: Coronavirus Disease 2019 (COVID-19) was announced by WHO as a pandemic. To prevent COVID-19, the government is seeking to provide a COVID-19 vaccine. Using vaccines is relatively safe but cannot be separated from the side effects of the vaccine, which are called AEFIs. AEFIs have symptoms such as pain, redness, swelling at the injection site, nausea and vomiting, fatigue, influenza, fever, muscle and joint pain, headache and serious allergic reactions.Method: This research is a type of descriptive analytic research with a survey approach. The samples of the research 95 people with method is purposive sampling. The instrument used in this study is the COVID-19 vaccine AEFI questionnaire, with the analysis used is univariate analysis.Results: The AEFIs that emerged after the AstraZeneca vaccine was administered to the community in the Public Health Center Sedayu II Bantul were mild local AEFIs with swelling, pain, redness and itching at the injection site. Systemic mild AEFI with symptoms of fever, headache, joint pain, arm muscle weakness and fatigue. Severe AEFI showed symptoms of arm muscle paralysis and severe allergic reactions. Other AEFIs with symptoms of insomnia and sleepiness.Conclusions: There was an AEFI after the AstraZeneca vaccination was carried out in the community in the Public Health Center Sedayu II Bantul. Health workers/nurses are expected to increase their knowledge and increase the attention of health workers/nurses to develop appropriate intervention strategies and participate in vaccination training to deal with AEFIs that occur in the community.